The Interdependence Between Donors and Investors: Liability of Hybridity, Entrepreneurial Ecosystem Affordances, and Venture Financing - Ofem, Brandon; Uzuegbunam, Ikenna; Nambisan, Satish (Entrepreneurship Theory and Practice, 2025)
This study investigates how spatial and digital affordances within entrepreneurial ecosystems (EEs) enable early-stage hybrid ventures to overcome the liability of hybridity and to secure funding from both philanthropic and equity funding sources. Using a simultaneous equation model with a U.S.-based sample of 2,723 hybrid ventures, we demonstrate that philanthropic and equity funding exhibit a statistically and economically significant complementary relationship. We further find that accelerator participation weakens this complementary relationship, while social media utilization strengthens it. These findings highlight the mechanisms through which EE-based affordances enhance hybrid ventures’ ability to navigate competing institutional logics and attract diverse funding sources.